Exploring the Core Components of Collaborative Continuing Professional Development (CCPD) in the Iranian Context - Sharifi Feriz, Zahra; Zeraatpishe, Mitra; Ashraf, Hamid; Zohoorian, Zahra (Assessment and Practice in Educational Sciences, 2026)
Collaborative Continuing Professional Development refers to ongoing learning activities. It aimed at enhancing teachers' professional growth through collaboration. This qualitative study explored the perceptions and practices of English as a Foreign Language (EFL) teachers regarding Collaborative Continuing Professional Development (CCPD). It involved semi-structured interviews with 30 teachers (23 university lecturers and 7 institute teachers) to collect in-depth insights into their experiences with CCPD, professional development, and collaboration. To analyze the data, the researchers used thematic analysis and MAXQDA software. The researchers identified seven themes for CCPD: policy and legal framework, active stakeholder participation, needs assessment and localization of content, collaborative learning methods, evaluation and feedback system, motivational and structural support, sustainability and future orientation. Overall, the study emphasized the importance of collaborative practices in continuous professional development for EFL teachers. It highlights that teachers who actively engage in CCPD not only improve their own teaching practices but also contribute to a broader culture of collaboration within their educational institutions. The findings suggest that teacher training programs can incorporate collaborative learning strategies to enhance the effectiveness of professional development.